2023
DOI: 10.1002/masy.202200027
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of ZnO – ZnFe2O4 Nanocomposites

Abstract: Zinc oxide (ZnO) and zinc ferrite (ZnFe 2 O 4 ) powders are synthesized using a sol-gel combustion method. The synthesized powders' crystal structure and microstructure are studied using X-ray diffraction (XRD), Fourier transformation spectroscopy (FTIR), and a field effective scanning electron microscopy (FESEM). XRD studies confirm the presence of nanocrystalline hexagonal wurtzite structure for ZnO and spinel phases for ZnFe 2 O 4 . The average crystallite size of the powders measured from XRD patterns is 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…On the other hand, ZnO and ZnFe 2 O 4 combine, revealing some synergistic effect. M. S. AlSalhi et al reported that ZnO-ZnFe 2 O 4 formed a hybrid nanocomposite that enhanced the transfer and separation of charges, resulting in the improved catalytic performance of heterostructure photocatalysts under visible light [39]. Furthermore, the incorporation of ZnFe 2 O 4 into ZnO extends the range of its absorption wavelength, especially in the visible and near-infrared regions, which show a high solar utilization efficiency and photovoltaic conversion efficiency for ZnO-ZnFe 2 O 4 [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ZnO and ZnFe 2 O 4 combine, revealing some synergistic effect. M. S. AlSalhi et al reported that ZnO-ZnFe 2 O 4 formed a hybrid nanocomposite that enhanced the transfer and separation of charges, resulting in the improved catalytic performance of heterostructure photocatalysts under visible light [39]. Furthermore, the incorporation of ZnFe 2 O 4 into ZnO extends the range of its absorption wavelength, especially in the visible and near-infrared regions, which show a high solar utilization efficiency and photovoltaic conversion efficiency for ZnO-ZnFe 2 O 4 [40,41].…”
Section: Introductionmentioning
confidence: 99%